Iron economy in Naegleria gruberi reflects its metabolic flexibility - Mach, Jan; Bíla, Jarmila; Ženíšková, Kateřina; Arbon, Dominik; Malych, Ronald; Glavanakovová, Marie; Nývltová, Eva; Sutak, Robert (International journal for parasitology, 2018)
Naegleria gruberi is a free-living amoeba, closely related to the human pathogen Naegleria fowleri, the causative agent of the deadly human disease primary amoebic meningoencephalitis. Herein, we investigated the effect of iron limitation on different aspects of N. gruberi metabolism. Iron metabolism is among the most conserved pathways found in all eukaryotes. It includes the delivery, storage and utilisation of iron in many cell processes. Nevertheless, most of the iron metabolism pathways of N. gruberi are still not characterised, even though iron balance within the cell is crucial. We found a single homolog of ferritin in the N. gruberi genome and showed its localisation in the mitochondrion. Using comparative mass spectrometry, we identified 229 upregulated and 184 down-regulated proteins under iron-limited conditions. The most down-regulated protein under iron-limited conditions was hemerythrin, and a similar effect on the expression of hemerythrin was found in N. fowleri. Among the other down-regulated proteins were [FeFe]-hydrogenase and its maturase HydG and several heme-containing proteins. The activities of [FeFe]-hydrogenase, as well as alcohol dehydrogenase, were also decreased by iron deficiency. Our results indicate that N. gruberi is able to rearrange its metabolism according to iron availability, prioritising mitochondrial pathways. We hypothesise that the mitochondrion is the center for iron homeostasis in N. gruberi, with mitochondrially localised ferritin as a potential key component of this process.
Keywords: biologický transport; Metabolism; anaerobióza; regulace genové exprese enzymů; Naegleria; spotřeba kyslíku; Oxygen Consumption; Biological Transport; Ferritin; hemerythrin; železo; Mass Spectrometry; protozoální proteiny; Anaerobiosis; Iron; zvířata; Protozoan Proteins; Hemerythrin; chromatografie kapalinová; Gene Expression Regulation, Enzymologic; Chromatography, Liquid; hmotnostní spektrometrie; Animals